Lattice network coding over Euclidean Domains - Vázquez-Castro, M. A. (2014)
We propose a novel approach to design and analyse lattice-based network coding. The underlying alphabets are carved from (quadratic imaginary) Euclidean domains with a known Euclidean division algorithm, due to their inherent algorithmical ability to capture analog network coding computations. These alphabets are used to embed linear p-ary codes of length n, p a prime, into n-dimensional Euclidean ambient spaces, via a variation of the so-called Construction A of lattices from linear codes. A study case over one such Euclidean domain is presented and the nominal coding gain of lattices obtained from p-ary Hamming codes is computed for any prime p such that p ≡ 1 (mod 4).